Evaluation of Antioxidant and Antimicrobial Activities of Drypetes perreticulata Gagnep. Extracts - Chen, Deli; Liu, Pinghuai; Xu, Qiongqing; Wang, Chunniu (Asian Journal of Chemistry, 2012)
The aim of this paper was to screen the petroleum ether, dichloromethane, ethyl acetate and methanol extracts of D. perreticulata leaves and stem. In this study, antioxidant, antimicrobial effects of D. perreticulata leaves and D. perreticulata stem were evaluated using DPPH and FRAP, disc diffusion method, MIC and MTT cytotoxicity assays, respectively. Results showed that petroleum ether, dichloromethane, ethyl acetate, methanol extracts of leaves and stem of D. perreticulata exhibited moderate antioxidant and antibacterial activity. EC50, FRAP value of DPSEA were 325.7 μg/mL and 3503.3 ± 63.2 μ mol Fe2+/g in DPPH, FRAP method, respectively. All the extracts showed no inhibitory effect on tested fungi strain, Candida albicans. The petroleum ether extracts exhibited a broad spectrum cytotoxicity activity, in which IC50 were from 76.79 to 682.5 μg/mL. Results demonstrated that the extracts prepared from D. perreticulata possess antioxidant activity in vitro and antibacterial properties. It is concluded that the D. perreticulata extracts can be useful as a natural antioxidant and a probable antibacterial agent.